Transcriptomic and metabolomic insights into the role of fliS in the pathogenicity of Pseudomonas plecoglossicida against Epinephelus coioides - Wu, Wensi; Zhao, Lingmin; Huang, Lixing; Qin, Yingxue; Zhang, Jiaonan; Zhang, Jiaolin; Yan, Qingpi (Frontiers in Marine Science, 2022)
Pseudomonas plecoglossicida is responsible for visceral white spot disease in economically valuable marine fish such as Larimichthys crocea and Epinephelus coioides. Based on RNA sequencing, we previously showed that P. plecoglossicida fliS gene expression is significantly up-regulated in E. coioides spleens during infection. Here, to explore the role of this gene in pathogenicity, RNA interference (RNAi) was performed to silence fliS in P. plecoglossicida, and the mutant with the best silencing efficiency (89%) was chosen for further studies. Results showed that fliS silencing significantly attenuated motility, chemotaxis, adhesion, and biofilm formation of P. plecoglossicida. Furthermore, E. coioides infected with the fliS-RNAi strain recorded no deaths and showed fewer pathogens in the spleen and fewer white spots on the spleen surface compared to those fish infected with the wild type P. plecoglossicida strain. RNAi of fliS significantly affected the spleen transcriptome and metabolome in infected E. coioides. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that the cytokine-cytokine receptor interaction pathway was the most enriched immune-related pathway, and the arginine biosynthesis pathway was the most enriched metabolism-related pathway. These findings suggest that fliS is a virulence gene of P. plecoglossicida and is involved in the regulation of motility, chemotaxis, adhesion, and biofilm formation, as well as the inflammatory and immune responses of E. coioides to P. plecoglossicida infection.